Oocyte Retrieval in Asymptomatic Patients Positive for SARS-CoV-2 - Allison Akers; Erika P. New; Shayne Plosker; Celso P. Silva; Rachel Sprague; Anthony N. Imudia (Case Reports in Obstetrics and Gynecology)
Objective. To report two cases of oocyte retrieval performed in asymptomatic SARS-CoV-2-positive patients. Design. Case report. Setting. Outpatient private practice infertility center. Patients. A 28-year-old woman at risk for OHSS who took her trigger injection prior to testing positive for SARS-CoV-2 and a 19-year-old oncofertility patient who tested positive prior to retrieval due to a family exposure. Both patients were asymptomatic. Main Outcome Measures. Cycle outcomes, patient safety, and staff safety. Results. Both patients underwent successful oocyte retrieval procedures without developing symptoms or complications from COVID-19. No staff members that cared for these patients developed symptoms of COVID-19. Conclusion. Worsening fertility outcomes and potential for psychological and financial burdens to the patient must be balanced with risk of perioperative complications in patients testing positive for SARS-CoV-2. As we continue to provide fertility care in a world with COVID-19, appropriate risk mitigation strategies should be implemented to minimize exposure to SARS-CoV-2.